Evaluación del comportamiento agronómico y productivo de dos variwedades de Maní (Arachis hypogaea L.) con diferentes densidades poblacionales de siembra en el recinto San José de Pijullo, cantón Urdaneta, provincia Los Ríos - Cervantes Limones, Jhalmar Eduardo (2017)
The peaments (Arachis hypogaea L.) is an oilseed that contributes to agricultural and industrial progress of the countries where is grown. The average annual production is 13 to 20 quintals/ha, peanuts are vegetable source of protein and unsaturated fats, it contains phytosterols that lower bad cholesterol from the body; and it provides minerals as sodium, potassium, iron, magnesium, iodine, copper and calcium. Globally, it seeded in 26 million hectares producing about 45 million tons per year. In Ecuador the main provinces where this oilseed is grown are: Manabi and Loja, with 88 % of the area planted. El Instituto Nacional de Investigaciones Agropecuarias - INIAP works in generating suitable for cultivation technologies. The objectives of this research were: i) validate the agronomic performance of two varieties of peanuts in the agro-ecological zone of San José de Pijullo. ii) To measure the effect of four sowing densities peanut on performance. iii) Conduct a Partial Budget Economic Analysis and calculate the Marginal Rate of Return. This trial was conducted in the province Los Rios, canton Urdaneta, paroquia Ricaurte, recinto San José de Pijullo. Design randomized complete block design was used in factorial arrangement of 2 x 4 x 3 repetitions. In Based on the analysis and interpretation of the results obtained in this trial we conclude: For Pijullo agro-ecological zone, the variety had the highest average yield was INIAP-383 Pintado with 1650.7 kg/ha. Plant densities studied had a significant influence on performance, the highest average was recorded with B2 density: 20 plants/m2 (200.000 plants/ha), with 1869.8 kg/ha at 14 % moisture. In the interactions of factors A x B; the highest average yield was recorded in the treatment T6: A2 B2 (INIAP-383 Painted with 20 plants/m2) with 1881.1 kg/ha. The variable that contributed to increase the yield of peanut was: Grains per plant (GP) with 77 %. The variety with higher yield potential, selected for this agro-ecological zone and planting time of June 10, 2015 was: INIAP-383 with 20 plants/m2.